Analisis Fabrikasi Desain Lamination Passive Mixing Microchannel Perangkat Mikrofluidik AcrylicMenggunakan Laser CO Daya Rendah - Badruzzaman Badruzzaman; Ario Sunar Baskoro; A. Rizal Siswantoro (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2016)
Microfluidics device has been applied in the biomedical fields to manipulate fluids in a channel network with the dimensions between 5-500 µm. Microfluidics device is manufactured by microfabrication process consists ofdesign, microstucturing and back-end process. One of microfluidics application is passive mixing microchannel. Inthis device, the fluids will flow through the channel without any moving part and pressure from outside to producemixing fluid. It is important to design the form of channel to produce a good lamination passive mixingmicrochannel. In this study, the process of channel design was performed. Low power CO2 laser was used formicrostucturing process as a cutting tool to produce microfluidic device on acrylic material. The parameters affectthe output of the cutting process are the laser power, cutting speed and the design of channel. Surface roughness ofdesigned channel was observed. Finally, back-end process was performed by joining process using thermalbonding method. From the experimental results, the design of lamination channel has an influence on allparameters to the surface roughnes.